Clinical practice guideline for the treatment of hormone-sensitive metastatic prostate cancer in the Peruvian Social Security (EsSalud) - Cuevas-Muñoz , Nelson (2024)
Introduction: This article summarizes the clinical practice guideline (CPG) for the treatment of metastatic hormone-sensitive prostate cancer in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for the treatment of adults with hormone-sensitive metastatic adenocarcinoma of the prostate with de novo or recurrent presentation and high or low metastatic volume in EsSalud. Methods: A guideline development group (GDG) was formed, which included specialist physicians and methodologists, who formulated clinical questions. Systematic searches were conducted for systematic reviews and - when deemed relevant - primary studies in PubMed during 2022. Evidence was selected to answer each of the clinical questions posed. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GEG used the GRADE methodology to review the evidence and formulate recommendations. The CPG was reviewed by external experts before its approval. Results: The CPG addressed 6 clinical questions, divided into 2 main topics: considerations on androgen deprivation therapy (ADT) and ADT combined with other therapies. Based on these questions, 10 recommendations were formulated (4 strong and 6 conditional), and 6 points of good clinical practice. Conclusion: Evidence-based recommendations were issued for the management of patients with this pathology.